Passive constructions in Setswana: Argument structure alternations from Lexical Mapping Theory perspective (JULACE: Journal of the University of Namibia Language Centre, 2018)
The paper analyses passive constructions in Setswana from morpho-syntactic view point, showing that the suffixation of a passive morpheme to the verb reduces the argument structure of the verb. Previous studies carried out in Setswana verbal suffixes have confined their investigations to these morphemes as elements of morphology but have failed to observe that these affixes overlap into syntax. Chebanne (1996) observes that in Setswana, verbal extensions can combine with a single verbal base but fail to observe the overlap into syntax. Further, the studies do not give any insight in the features that Setswana shares with other Bantu languages. The passive construction in Setswana, like in other Bantu languages, is a bit complex in the sense that the verbal extension –iw brings into effect the dropping of the subject, and the object becomes the grammatical subject, thus rendering the transitive verb, such as, apaya ‘cook’ intransitive. Conversely, other derivational suffixes, such as applicative and causative, increase the verb’s arguments by two. For instance, the suffixation of the verbal suffix –el suggests an entity carrying out the action and somebody benefiting. The paper also compares passive with other verbal extensions such as neuter, applicative, causatives and reciprocals. It shows that while the passive occurs with most verbs and other verbal extensions, such as, applicative or causative suffixes, the neuter is rigid in occurring with other verbal extensions. The paper also appeals to Lexical Mapping Theory, whose role is to constrain mapping relations between thematic roles, such as an agent or patient and the corresponding grammatical functions, such as the subject, patient and oblique that have been subcategorized for by predicates
Keywords: morpho-syntactic; Setswana; Bantu languages; passive construction; Lexical Mapping Theory